2019
DOI: 10.3390/cancers12010056
|View full text |Cite
|
Sign up to set email alerts
|

Ovatodiolide Suppresses Oral Cancer Malignancy by Down-Regulating Exosomal Mir-21/STAT3/β-Catenin Cargo and Preventing Oncogenic Transformation of Normal Gingival Fibroblasts

Abstract: Oral squamous cell carcinoma (OSCC) is among the most commonly diagnosed malignancies in the world. Patients with OSCC often develop treatment resistance, resulting in a poor prognosis. Mounting evidence indicates that interactions between cancerous cells and other components of the tumor microenvironment (TME) determine their response to treatment. Herein, we examined the role of cancer stem cell-derived extracellular vesicles (CSC_EVs) generated from CAL27 and SCC-15 OSCC cells in the development of cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…Targeting miR-155 or the exosome secretion of PDAC cells effectively attenuated the gemcitabine resistance in PDAC cell lines and in xenograft nude mice [ 106 ]. Other cancer sEV-associated microRNAs, such as miR-21 and miR-1246, have also been found to be selectively enriched in cancer sEVs and considered as therapeutic targets [ 107 , 108 ]. Since cancer sEVs selectively encapsulate certain microRNA species [ 25 , 109 , 110 , 111 ], targeting cancer sEV-associated microRNAs will continue to be an attractive strategy for the development of new cancer therapeutics.…”
Section: Evs As Potential Therapeutic Targets In Cancermentioning
confidence: 99%
“…Targeting miR-155 or the exosome secretion of PDAC cells effectively attenuated the gemcitabine resistance in PDAC cell lines and in xenograft nude mice [ 106 ]. Other cancer sEV-associated microRNAs, such as miR-21 and miR-1246, have also been found to be selectively enriched in cancer sEVs and considered as therapeutic targets [ 107 , 108 ]. Since cancer sEVs selectively encapsulate certain microRNA species [ 25 , 109 , 110 , 111 ], targeting cancer sEV-associated microRNAs will continue to be an attractive strategy for the development of new cancer therapeutics.…”
Section: Evs As Potential Therapeutic Targets In Cancermentioning
confidence: 99%
“…Uptake of miR-21-containing EVs into recipient fibroblasts actively promotes CAF differentiation via an increase in PI3K signaling [99,104]. The same study found that CAF differentiation correlated with increased expression of additional oncogenic proteins in recipient cells, including β-catenin, signal transducer and activator of transcription 3 (STAT3), the mammalian target of rapamycin (mTOR), and TGF-β [99].…”
Section: Mirnamentioning
confidence: 92%
“…MiRNAs are among the most abundant cargo found in EVs; as such, it is unsurprising that EV-mediated miRNA transfer from cancer to stromal cells plays an important role in promoting CAF differentiation. To date, at least two dozen miRNAs have been found to be responsible for promoting EV-mediated CAF differentiation in a variety of cancer types [11,95,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Uptake of miRNA-containing EVs into recipient cells results in altered expression of key signaling pathways, many of which have a known oncogenic or tumor-suppressive role, which leads to the adoption of a CAF phenotype.…”
Section: Mirnamentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [ 136 ] proved that EVs released from oral squamous cell carcinoma (OSCC) cells correlate with an increased level of β-catenin, the expression of several oncogenic markers, the reprogramming of normal gingival fibroblasts into CAFs, increased metastasis, stemness reprogramming, chemoresistance, and poor patients’ survival ( Table 3 ).…”
Section: Extracellular Vesicles and The Wnt Pathwaymentioning
confidence: 99%